Practical evaluation of a physical-therapeutic exercise program in patients with amyotrophic lateral sclerosis/Valoración práctica de un programa de ejercicios físico-terapéuticos en pacientes con esclerosis lateral amiotrófica - Yordán Cañadilla Barrios; Magda Mesa Anoceto; Jerry Bosque Jiménez; Rodolfo Ruvenio Vidaurreta Bueno; Annia Caridad Cañete Rojas (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
Given the need to design specific intervention strategies for patients with Amyotrophic Lateral Sclerosis (ALS), incorporating Rehabilitation and Physical Culture contents from an integrative perspective, a physical-therapeutic exercise program was developed specifically for these patients at the Institute of Neurology and Neurosurgery, to contribute to slow the progression of the disease, attenuating symptoms, signs and complications. The aim of the study was to evaluate in practice the efficacy of the physical-therapeutic exercise program applied. A longitudinal study was conducted and used the pre-experiment of samples related to patients diagnosed with ALS in the period 2014-2019, evaluating the results of the first three months of application, with follow-up planned after these. In the processing of the recorded data, the empirical distribution of frequencies and their graphical representations; descriptive measures (arithmetic mean and standard deviation); binomial test; test 2 for two independent samples, applied to contingency tables; Student's t-test for related samples, and Shapiro Wilks test were used. As a result, 71.05 % of the patients included in the study presented a plateau in the behavior of their clinical picture, which corroborates the benefits of the program and its effectiveness, through the use of physical-therapeutic exercises, respiratory and nutritional support, contributing to the delay of the progression of the disease from one stage to the other of the functional classification.